PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN PADA FASTGLOBAL EXPRESS - Munir Azhari (Aliansi : Jurnal Manajemen dan Bisnis, 2020)
The Influence of work Stress on Employee Performance at Fastglobal Express. Based on the significant testbetween the independent X variable (work stress) and the dependent Y variable (employee performance) for the workStress variable (X), the t-count value is 22.960 while the t-table value for N = 100 is 1.666 then 22.960 1.666 witha significant effect of t 0, 05 or t count t table. Based on the results of the t test that in fact the work stress variable(X) has a significant relationship to the Employee Performance variable (Y) where the value of t is greater than t table, thus it can be concluded that Ho is rejected and Ha is accepted. The results of the analysis of the work stress obtained a value of 0.918 so that it can be concluded that it is positive and the level of influence is forceful.